Empowering minds: how self-efficacy, self-esteem, and social support drive digital mental health engagement - Kok Wah, Jack Ng (Frontiers in Public Health, 2025)
IntroductionDespite the rapid growth of research in digital health, there is a significant gap in understanding how psychological factors such as self-efficacy, self-esteem, and perceived social support collectively influence digital mental health engagement, particularly within the Malaysian context. While previous studies have explored these constructs individually, few have examined their integrated effects on user engagement with e-health platforms. The study aims to fill that gap by exploring the direct relationships between self-efficacy, self-esteem, and perceived social support with digital mental health engagement, while also analyzing the mediating role of perceived social support. The novelty of the research lies in integration of these psychological constructs into a unified conceptual framework to provide a more comprehensive understanding of digital mental health engagement.MethodsUsing a quantitative, cross-sectional design, the study surveyed 400 active Malaysian e-health users through a self-administered questionnaire. The survey used validated scales to measure self-efficacy, self-esteem, perceived social support, and engagement with digital mental health platforms. Structural Equation Modeling (SEM) was employed to test five hypotheses regarding direct and mediated relationships.ResultsDemographic analysis revealed that many participants were female (71.3%), aged between 25 and 45 years (76.6%), and from higher income brackets (RM5,001–RM20,000). WhatsApp (400 users) was found to be the most popular tool, followed by Facebook (387 users) and Instagram (371 users), highlighting the importance of these platforms in connectivity and information sharing. The study found that perceived social support had the strongest direct effect on digital mental health engagement (β = 0.523), followed by self-esteem (β = 0.384) and self-efficacy (β = 0.236). Additionally, perceived social support significantly mediated the impact of both self-efficacy and self-esteem on engagement.DiscussionThese findings underscore the importance of fostering supportive digital environments to enhance users’ confidence and self-worth. However, the cross-sectional nature of the study limits causal interpretations, and the localized sample restricts generalizability. Future research should incorporate longitudinal methods and explore cultural differences. Overall, the study contributes to the development of effective digital mental health engagement strategies in Malaysia and beyond.